2004
DOI: 10.1007/s00253-004-1740-1
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of a β-1,4-endoglucanase from an endophytic Bacillus pumilus strain

Abstract: Endophytes comprise mainly microorganisms that colonize inner plant tissues, often living with the host in a symbiotic manner. Several ecological roles have been assigned to endophytic fungi and bacteria, such as antibiosis to phytopathogenic agents and plant growth promotion. Nowadays, endophytes are viewed as a new source of genes, proteins and biochemical compounds that may be used to improve industrial processes. In this study, the gene EglA was cloned from a citrus endophytic Bacillus strain. The EglA enc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
22
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 48 publications
4
22
0
1
Order By: Relevance
“…It was observed that the optimum condition of enzyme activity by the soldier termites was pH 8 and temperature 50 °C which are in agreement with that reported by Lima et al (2005) for Bacillus pumilus strain. The optimum temperature value was the same in comparison to that obtained with the cellulase from the Reticulitermes speratus (Kolbe), a Japanese Subterranean Termite (Watanabe et al, 1997) and very close to that from the digestive tract of the termite Macrotermes mulleri, in which an optimum temperature of 55 o C was observed (Rouland et al, 1988).…”
Section: Discussionsupporting
confidence: 81%
“…It was observed that the optimum condition of enzyme activity by the soldier termites was pH 8 and temperature 50 °C which are in agreement with that reported by Lima et al (2005) for Bacillus pumilus strain. The optimum temperature value was the same in comparison to that obtained with the cellulase from the Reticulitermes speratus (Kolbe), a Japanese Subterranean Termite (Watanabe et al, 1997) and very close to that from the digestive tract of the termite Macrotermes mulleri, in which an optimum temperature of 55 o C was observed (Rouland et al, 1988).…”
Section: Discussionsupporting
confidence: 81%
“…The search for new cellulases with properties more suitable for industrial application remains a constant effort (Lima et al, 2005). In addition, new thermophilic cellulases are being exploited in order to make the relevant industrial processes more efficient and economical (Liang et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Endophyte microorganisms colonize inner plant tissues, living symbiotically with the host species (Azevedo et al, 2000). These microorganisms have been investigated as a source of new genes and proteins for use in industrial processes (Stamford et al, 2001(Stamford et al, , 2002Pleban et al, 1997;Reddy et al, 1996;Moy et al, 2002;Lima et al, 2004).…”
mentioning
confidence: 99%
“…isolated from Citrus were evaluated for cellulolytic activity (Lima et al, 2004). The Bacillus pumilus strain CL16 showed high cellulase activity and was selected for further studies.…”
mentioning
confidence: 99%